The outcome of fresh frozen allografts in bone healing: a prospective study, in a tertiary care centre, India - Yelavarthi, Raghu; Pingle, Jairamchander; Palakuri, Sadhan (International Journal of Research in Orthopaedics, 2022)
Background: Massive bone loss is a major problem in modern orthopaedics. Allograft use in clinical practice has become a desirable option. Allografts are used to reconstruct bony defects in different disorders in orthopaedic surgeries. Fresh frozen allograft is a reconstructive biologic option for osseous defects. This article evaluates the outcome of fresh frozen allografts in bone healing in different orthopaedic procedures. Methods: Prospective non-randomized trial was conducted in 136 patients of any age presenting to orthopaedic OPD with bone defects/disorders requiring bone grafting in a tertiary care centre. Ann et al radiological criteria for new bone formation, was used for grading outcome. Results: The age of the patients varied between 12-76 years. About 8.1% patients belonged to 10-25 years age group, 39% to 26-40 years, 25% to 41-50 years, 15.4% to 51-60 years, 6.6% to 61-70 years and 5.9% to above 70 years age group. Mean age was 39.7 years. There were 61% male and 39% female patients. Minimum follow-up period was 1 month and maximum 4 years. Allografting was performed for 46 fractures with bone loss, 33 fractures with non-union/delayed union, 25 arthroplasties, 13 arthrodeses and 19 tumours. Follow-up results at two months showed that 84.6% had good, 12.5% had fair and 2.9% had bad results. Conclusions: Allografting is one of the best options available for bone defects, especially in younger patients with a high life expectancy because of its potential durability.